Supplementation with Standardized Green/Black or White Tea Extracts Attenuates Hypertension and Ischemia-Reperfusion-Induced Myocardial Damage in Mice Infused with Angiotensin II - Mario de la Fuente-Muñoz; Marta Román-Carmena; Sara Amor; María C. Iglesias-de la Cruz; Patricia Martorell; Sonia Guilera-Bermell; Reme García Bou; Antonio M. Inarejos-García; Ángel L. García-Villalón; Miriam Granado (Antioxidants)
Arterial hypertension has a high prevalence in the population and is considered both a cardiovascular disease and an important risk factor for the development of other cardiovascular diseases. Tea consumption shows antihypertensive effects due to its composition in terms of bioactive substances such as flavan-3-ols and xanthines. The aim of this study was to assess the possible beneficial effects of two tea extracts, one of white tea (ADM® White Tea; WTE) and another one composed of a mixture of black tea and green tea (ADM® Tea Complex; CTE), on the cardiovascular alterations induced by angiotensin II (AngII) infusion in mice. For this purpose, four groups of C57BL/6J male mice were used: (1) mice fed on a standard diet for 8 weeks and infused with saline for the last 4 weeks (controls); (2) mice fed on a standard diet for 8 weeks and infused with AngII for the last 4 weeks (AngII); (3) mice fed on a standard diet supplemented with 1.6% WTE and infused with AngII for the last 4 weeks (AngII + WTE); (4) mice fed on a standard diet supplemented with 1.6% TC and infused with AngII for the last 4 weeks (AngII + CTE). Both tea extracts exerted anti-inflammatory and antioxidant effects in arterial tissue and reduced AngII-induced endothelial dysfunction in aorta segments. Moreover, supplementation with WTE or CTE reduced the Ang-II-induced overexpression of AT1R and increased AngII-induced downregulation of AT2R in arterial tissue. However, only supplementation with CTE significantly increased the circulating levels of angiotensin 1-7 and reduced systolic blood pressure. In the heart, supplementation with both tea extracts attenuated AngII-induced cardiac hypertrophy and reduced ischemia-reperfusion-induced oxidative stress and apoptosis in myocardial tissue. In conclusion, supplementation with WTE or CTE attenuates AngII-induced cardiovascular damage through their anti-inflammatory, antioxidant, and antiapoptotic effects. In addition, supplementation with CTE also exerts antihypertensive effects, and so it may constitute an avenue through which to support cardiovascular health.